2018
DOI: 10.1016/j.bbr.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural responsivity to food cues in relation to food preferences, but not appetite-related hormone concentrations after RYGB-surgery

Abstract: RYGB leads to changed responsivity of the frontoparietal control network that orchestrates top-down control to high-energy food compared to low-energy food and non-food cues, rather than in reward related brain regions, in a satiated state. Together with correlations with the shift in food preference from high- to low-energy foods this indicates a possible role in new food preference formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 62 publications
7
40
3
Order By: Relevance
“…The present study found more healthy patterns of food liking among those women who were more successful at bariatric surgery. This agrees with previous studies that report less liking for sweets and high fat food across bariatric surgery [24,25,26,37,81,82], including the association with greater success in weight loss [29] and more favorable metabolic profile [31]. We showed reduction of liking of sweetness in the candy probe and with survey liking of sweets and sweet drinks (i.e., unhealthy foods), as well as significant correlations between the liking of sample candy and survey liking of sweet (sweet candy) and spicy or flavorful (spicy candy) foods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study found more healthy patterns of food liking among those women who were more successful at bariatric surgery. This agrees with previous studies that report less liking for sweets and high fat food across bariatric surgery [24,25,26,37,81,82], including the association with greater success in weight loss [29] and more favorable metabolic profile [31]. We showed reduction of liking of sweetness in the candy probe and with survey liking of sweets and sweet drinks (i.e., unhealthy foods), as well as significant correlations between the liking of sample candy and survey liking of sweet (sweet candy) and spicy or flavorful (spicy candy) foods.…”
Section: Discussionsupporting
confidence: 93%
“…The liking survey is feasible for a clinical setting, taking minutes to complete, and if online, limited time to process. Our work extends previous findings [24,25,26,37,81,82] through use of this feasible clinical measure that can provide a valid and reliable index of diet quality and health behavior. Our liking survey was formed into a diet quality index with construct and criterion validity similar to the Healthy Eating Index [39], and replicated our work with a separate sample of women with morbid obesity in a bariatric treatment setting [41].…”
Section: Discussionsupporting
confidence: 85%
“…Concerning the AEA and 2-AG levels, present results are in apparent contrast with those published previously which might be due to the differences in subjects' demographic characteristics, intervention and sample pretreatment [32][33][34][35].…”
Section: Discussioncontrasting
confidence: 99%
“…Oral taste of high vs. low-fat milkshake independent of sugar content involved in the PCC activation difference that predicts future weight loss (Yokum and Stice, 2019 ). In a recent study, Roux-en-Y gastric bypass surgery-induced decreased liking of high-fat/high-sugar food odors was accompanied by an increased precuneus activation (Zoon et al, 2018 ). Taken together, the activation of the precuneus in responses to high-fat food odors may be protective against future weight gain.…”
Section: Discussionmentioning
confidence: 99%